Pengaruh Ukuran Perusahaan, Kualitas Manajemen, dan Kompleksitas Bisnis terhadap Kepatuhan Standar Audit - Chandra Kurniawan; Cris Kuntadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the influence of company size, management quality, and business complexity on audit standard compliance. Compliance with audit standards is important in ensuring the quality of audit reports and increasing public trust in the audit profession. Company size, management quality, and business complexity are considered factors that can influence auditor compliance with audit standards. This research uses data from audit reports of companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. Data analysis was carried out using multiple linear regression. The research results show that company size and management quality have a positive effect on compliance with audit standards, while business complexity has a negative effect. These findings provide implications for regulators and the audit profession to increase compliance with audit standards through improving the quality of company management and managing business complexity.